2017
DOI: 10.1002/ejsp.2328
|View full text |Cite
|
Sign up to set email alerts
|

Pride and punishment: Entitled people's self‐promoting values motivate hierarchy‐restoring retribution

Abstract: What is the purpose of punishment? The current research shows that for entitled people—those with inflated self‐worth—justice is about maintaining societal hierarchies. Entitled people more strongly hold self‐enhancing values (power and achievement; Studies 1 and 3). They are also more likely, when thinking about justice for offenders, to adopt a hierarchy‐based justice orientation: Perceptions that crime threatens hierarchies, motives to restore those hierarchies, and support for retribution (Studies 2 and 3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 52 publications
1
28
0
Order By: Relevance
“…The current research showed that support for retribution as a purpose of punishment is related to two factors: (1) the perceiver's preference for hierarchical social structure and (2) the criminal offender's status, or position in that hierarchy. These findings support hypotheses based on previous findings, which show that people may support retribution when concerned about regulating hierarchies (Gerber & Jackson, ; Okimoto et al ., ; Pratto et al ., ; Redford & Ratliff, ; Sidanius et al ., ; Wenzel et al ., ). We expected that people who prefer hierarchies would more strongly support retribution: not uniformly, but more strongly for low‐status offenders.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The current research showed that support for retribution as a purpose of punishment is related to two factors: (1) the perceiver's preference for hierarchical social structure and (2) the criminal offender's status, or position in that hierarchy. These findings support hypotheses based on previous findings, which show that people may support retribution when concerned about regulating hierarchies (Gerber & Jackson, ; Okimoto et al ., ; Pratto et al ., ; Redford & Ratliff, ; Sidanius et al ., ; Wenzel et al ., ). We expected that people who prefer hierarchies would more strongly support retribution: not uniformly, but more strongly for low‐status offenders.…”
Section: Discussionmentioning
confidence: 99%
“…The current results join others in suggesting that support for retribution is related to hierarchy concerns (Gerber & Jackson, ; Okimoto et al ., ; Pratto et al ., ; Redford & Ratliff, ; Sidanius et al ., ; Wenzel et al ., ), but they also sharpen our view of that relationship by showing that it is moderated by offender status. While these previous findings suggest a uniform magnitude with which hierarchy preferences motivate punishment, the current research showed that hierarchy preferences motivate retributive punishment selectively, depending on the position of the offender in that hierarchy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, people higher in entitlement attach importance to achievement in life (Redford & Ratliff, 2018), congruent with the expertise and social value required to attain prestige.…”
Section: Entitlement and Status Motivationmentioning
confidence: 99%